2019
DOI: 10.1093/llc/fqz036
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach to lexical polysemy in Ancient Greek

Abstract: Language is a complex and dynamic system. If we consider word meaning, which is the scope of lexical semantics, we observe that some words have several meanings, thus displaying lexical polysemy. In this article, we present the first phase of a project that aims at computationally modelling Ancient Greek semantics over time. Our system is based on Bayesian learning and on the Diorisis Ancient Greek corpus, which we have built for this purpose. We illustrate preliminary results in light of expert annotation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Many studies rely on hand-picked examples (e.g., Wijaya and Yeniterzi, 2011;Rodda et al, 2017) or human judgements (e.g., Tredici et al, 2018). Some studies have performed evaluations based on dictionary data (e.g., Cook et al, 2014;Basile and McGillivray, 2018), manual annotation of dictionary senses in corpora (McGillivray et al, 2019), and manual annotation of word types (Kenter et al, 2015), but this approach is not well-suited for recent, yet-to-berecorded changes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies rely on hand-picked examples (e.g., Wijaya and Yeniterzi, 2011;Rodda et al, 2017) or human judgements (e.g., Tredici et al, 2018). Some studies have performed evaluations based on dictionary data (e.g., Cook et al, 2014;Basile and McGillivray, 2018), manual annotation of dictionary senses in corpora (McGillivray et al, 2019), and manual annotation of word types (Kenter et al, 2015), but this approach is not well-suited for recent, yet-to-berecorded changes.…”
Section: Introductionmentioning
confidence: 99%
“…data that differs considerably from the training data. Not all these factors might be equally problematic: for the computational modelling of Greek lexical meaning, for example, McGillivray et al (2019) found that genre is a more important factor than time, and argue that "literary Classical Greek is conservative when it comes to lexical semantics" (I also found similar results in my own experiments with meaning processing: see Keersmaekers 2020b: 119). As a complicating factor, there is a complex interplay between genre, diachrony and dialectal variation in literary Greek: some examples include Atticistic tendencies in postclassical Greek texts (i.e.…”
Section: Extralinguistic Variationmentioning
confidence: 74%
“…Recent years have seen an increased interest on the application of such methods for modelling semantic change to DH research, primarily using unsupervised methods (McGillivray et al, 2019;Soni et al, 2021). However, in order to be useful, analyses for DH research require a high degree of granularity on highly complex datasets and this has not yet been achieved by state-of-the-art methods.…”
Section: Related Workmentioning
confidence: 99%